The Tactical Object Monitoring System for Defense Operations Using the Concept of Object-Oriented Programming (OOP) with Python Programming Language - Rahmandhala, Ilvan Dino; Asep Adang Supriyadi; Yosef Prihanto; Ahmad Farid; Muhamad Samingan (CV. AFDIFAL MAJU BERKAH, 2025)
Information and communication technology is currently very important in the defense field, including in the development of tactical object monitoring systems for defense operations. One approach used is to apply the concept of object-oriented programming OOP using the Python programming language. This research uses data processing methods using the Python programming language with the help of Google Colab. In its implementation, this research creates two main classes, namely the Sensor Class and the Tactical Map Class. The Sensor Class functions to represent physical sensors in code form, with attributes of identity, location, and sensor status. The Tactical Map class serves as a representation of a tactical map used to manage and visualize objects, such as sensors, within a certain area. The development of a defense operation tactical object monitoring system by applying OOP concepts using the Python programming language has several benefits, such as easier system setup and maintenance, as well as the development of new features without disrupting existing functions. The application of OOP concepts using the Python programming language can be one of the effective approaches in developing a tactical object monitoring system for defense operations. This approach can improve the efficiency and effectiveness of military operations by utilizing modern technology, as well as provide various benefits in terms of system setup, maintenance, and development.